2013
DOI: 10.1111/apt.12292
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: colonoscopic post‐polypectomy bleeding in patients on continued clopidogrel therapy

Abstract: SUMMARY BackgroundCurrent guidelines recommend the cessation of clopidogrel therapy 5 days and 7-10 days prior to colonoscopic polypectomy. Recent studies have advocated for continued clopidogrel as post-polypectomy bleeding (PPB) rates have been similar to those in the general population not on antithrombotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Manocha et al[25] demonstrated PPB rates of patients on aspirin and NSAIDs vs those not on aspirin or NSAIDs (3.2% vs 3.0%). In contrast, polypectomy on clopidogrel is likely to have increased risk for PPB[8]. It might be prudent to postpone polypectomy for high thrombotic risk patients taking clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Manocha et al[25] demonstrated PPB rates of patients on aspirin and NSAIDs vs those not on aspirin or NSAIDs (3.2% vs 3.0%). In contrast, polypectomy on clopidogrel is likely to have increased risk for PPB[8]. It might be prudent to postpone polypectomy for high thrombotic risk patients taking clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…120 Polyp size was less than 10 mm in 88% of the cases, and the proportion of patients on DAPT ranged from 54% to 87.8%. [121][122][123] There was an overall increased risk of PPB (RR, 2.54; 95% CI 1.68 to 3.84) and of delayed PPB (RR, 4.66; 95% CI 2.37 to 9.17).…”
Section: Polypectomy On Antithrombotic Therapymentioning
confidence: 92%
“…Another meta-analysis that included five studies demonstrated an increased risk of delayed but not immediate PPB on clopidogrel. 120 A prospective study including 823 patients focused on cold polypectomy (using forceps or snare method) with a mean polyp size of 4.7±1.3 mm 91 ; 15% of the patients were taking low dose aspirin or ticlopidine. The risk of immediate PPB was increased in patients on continued APAs (6.2% vs 1.4%; p<0.001) but all bleeding episodes were successfully treated during the procedure, and no delayed PPB was observed.…”
Section: Polypectomy On Antithrombotic Therapymentioning
confidence: 99%
“…Metz et al showed a significant association between PPB and aspirin, but the study was conducted on large colonic lesions [20]. According to evidence from a meta-analysis [21], thienopyridines such as clopidogrel increase the risk of delayed PPB (pooled relative risk for PPB of 2.54; 95% CI, 1.68–3.84; p <0.00001). ESGE guidelines recommend interruption of thienopyridines before polypectomy only if the patient had no recent thrombotic event or a coronary drug-eluting stent placed >12 months previously [13].…”
Section: Discussionmentioning
confidence: 99%